Review of Global Capitalism and the Crisis of Democracy by Jerry Harris. Issue 2 (3rd April 2018) - Murray, Georgina
ABSTRACT: Jerry Harris's optimistic book shows how capitalism has remorselessly moved to end Keynesian social justice measures over the globe and consequently destroy opportunities for us moving toward democracy. He shows how class power has moved back from its brief Keynesian respite, falling effortlessly into patterns of neoliberal political, social and economic extremes. He looks for alternatives beyond state-centred experiments as different parts of the global transition of the capitalist experiences. He reviews possible transitional alternatives to continuous capitalism within green alternatives and other alternatives in Italy, Venezuela, Bolivia and Greece, and he finishes by asking questions about what a real post-liberal democracy needs to look like.